Behavior Analysis in the War on Poverty: The Therapeutic Workplace Wage Supplement Program. (October 2022) - Subramaniam, Shrinidhi; Holtyn, August F.; Silverman, Kenneth
Poverty presents a profound burden on health. Financial incentives can shape behavior to benefit individuals living in poverty and to benefit society. As current research shows, large-scale wage supplement programs (i.e., those that provide cash assistance for working) can sometimes increase employment, but tend not to address health problems like addiction. As proof of concept, the Therapeutic Workplace intervention treated addiction, increased employment, and reduced poverty in adults with long-term unemployment and opioid use disorder. The Therapeutic Workplace also developed academic skills, encouraged job readiness, enhanced engagement with employment services, and improved mood and quality of life. Granted, in this and similar trials, some participants did not become employed and many relapsed to drug use or were unemployed after the intervention ended. Continued battles in the war on poverty include identifying evidence-based methods to promote steady employment in high-wage jobs and maintaining positive health outcomes long term.